An Analysis of Code Mixing in Students and Teacher Interaction in Narrative Texts in SMP Negeri 3 Busungbiu, Buleleng - Ayu Chandra Ken Ningrum (Language-Edu, 2019)
Code mixing happens in bilingual or generally in multilingual society. It also happened in SMP Negeri 3 Busungbiu, a Junior High School, Busungbiu District of Buleleng Regency in Bali. The students often mixed English and Indonesian to express their idea during the English lesson. Based on the structure, the kinds of code mixing are in the forms of word, phrase, baster, repetition, idiom and clause. The research used descriptive qualitative and descriptive quantitative. The subject of the study was 9th grade students in class A and the English teacher of State Junior High school (SMPN) 3 Busungbiu, Buleleng, The study used recording and interview sheet.  From the research, the writer concluded that the highest number of code mixing in students’ transcript is code mixing in form of word level which attains 20 data and the fewest number of codes mixing in students’ and teacher transcript is code mixing in form of idiom level which has no data. The students’ reasons to do code mix were that they felt shy to speak English, were afraid in doing mistakes when they spoke English, and they lost the idea when they began to speak English. The English teacher also explained that the reason she used code mix was to help the students understand the meaning of English sentences easily and stimulate students to speak. Based on the classification of code mix done during the research, the researcher did not find code mix in idiom level from the two speaking transcripts because the students did not have many vocabularies in English. The result of this research may help the readers to know that code mixing often found in students learning foreign language, especially English.  This result of this research is expected as a feedback in improving the teaching process so students can improve their English knowledge without depending on the use of code mix. Keywords: bilingualism,code mix, teaching learning process